Light‐Driven and Light‐Guided Microswimmers. (19th February 2016) - Li, Wei; Wu, Xiaoran; Qin, Hong; Zhao, Zhongqiang; Liu, Hewen
Abstract : Light‐driven swimming particles hold great potential in wide applications ranging from next‐generation drug delivery to versatile microrobotic devices. It is desired that the self‐propelled microparticles should swim not only autonomously but also directionally to achieve their goals in their potential applications. This paper presents the first example of fully organic colloidal particles of a spiropyran‐terminated hyperbranched polymer that can be driven and meanwhile steered by a UV light source, swimming straight towards the UV source. The mean‐square velocities of the photochromic suspension particles are about 20 μm s −1, and increase to about 54 μm s −1 with the addition of NaCl of 0.5%. The phototactic propulsion is supposed to be originated from the UV irradiation‐induced interfacial tension gradient on the surface of the colloidal particles. This finding allows for the design of new microengines for next‐generation drug delivery systems, microrobotic devices, and self‐adaptive photocatalysts, etc. Abstract : Colloidal particles of a spiropyran‐terminated, photochromic hyperbranched polymer can autonomously swim toward a UV source like a phototactic microorganism. The self‐propelled phototactic colloidal particles may find applications in optically guided micro‐robotic systems for transport, delivery and diagnosis, and self‐adaptive photocatalysts, etc.